EVALUATION OF POLICY TRANSFORMATION IN THE DISRUPTION ERA IN THE EFFORT TO ACHIEVE FINANCIAL MANAGEMENT PERFORMANCE TARGETS BASED ON THE JOB SATISFACTION LEVELS OF EDUCATIONAL FINANCIAL MANAGERS AT NORTH SUMATRA UNIVERSITY - Erjan Fikry Antari; Prihatin Lumbanraja; R. Hamdani Harahap (CV. Radja Publika, 2025)
This research aims to determine the level of satisfaction and expectations of Financial Management Education Personnel regarding USU's efforts and achievements in the Era of Disruption in adjusting rules/regulations and digital transformation in financial management and in the management of financial management education personnel, as well as to determine the level of satisfaction and expectations regarding efforts and achieving USU's Financial Management Performance Targets in the Era of Disruption. This research uses mixed methods research (MMR), which integrates elements of qualitative and quantitative methods in one study. The population in this study was all financial management educational staff in 48 (forty eight) work units within USU with a total of 124 respondents. The data analysis methods used are the Customer Satisfaction Index (CSI) method, the Importance Performance Analysis (IPA) method and the Gap Analysis Method (GAP). The results obtained in this research show that the level of satisfaction of financial management education staff with the adaptation of rules/regulations and digital transformation in financial management in the era of disruption is 79.8% in the satisfied category, adaptation of financial management rules/regulations is a top priority, but there are no achievements in line with expectations. In the management of educational staff, financial management was 70.14% in the satisfied category with 5 (five) main priority indicators consisting of performance-based remuneration, implementation of a digital performance measurement system, increasing transparency and accessibility of information, use of a digital talent management system and analysis prediction data, as well as objectivity in selection, but there has been no achievement as expected. Meanwhile, the achievement of the Financial Management Performance Target was 76.82% in the satisfied category, with 2 (two) variables being the main priority, namely financial stability and increasing alternative income, but there has been no achievement as expected.